Functional differences in the mu opioid receptor SNP 118A>G are dependent on receptor splice‐variant and agonist‐specific recruitment of β‐arrestin - Casey Patrick; Utibeabasi Ettah; Vu Nguyen; Caitlin Hart; Evan Atchley; Krishna Mallela; Robert I. Scheinman; Andrew A. Monte (Wiley, 2024)
Abstract The OPRM1 gene codes for the mu opioid receptor (MOR) and polymorphisms are associated with complex patient clinical responses. The most studied single nucleotide polymorphism (SNP) in OPRM1 is adenine (A) substituted by guanine (G) at position 118 (118A>G, rs1799971) leading to a substitution of asparagine (Asn) for aspartic acid (Asp) at position 40 in the N terminus of the resulting protein. To date, no structural explanation for the associated clinical responses resulting from the 118A>G polymorphism has been proposed. We utilized computational modeling paired with functional cellular assays to predict unstructured N‐ and C‐terminal regions of MOR‐1. Using molecular docking and post‐docking energy minimizations with morphine, we show that the extracellular substitution of Asn at position 40 alters the cytoplasmic C‐terminal conformation, while leaving the G‐protein binding interface unaffected. A real‐time BRET assay measuring G‐protein and β‐arrestin association with MOR r generated data that tested this prediction. Consistent with this in silico prediction, we show changes in morphine‐mediated β‐arrestin association with receptor variants with little change in morphine‐mediated G‐protein association comparing MOR‐1 wild type (WT) to MOR‐1118A>G. We tested the system with different opioid agonists, the OPRM1 118A>G SNP, and different MOR splice variants (MOR‐1 and MOR‐1O). These results are consistent with the observation that patients with the 118A>G OPRM1 allele respond more readily to fentanyl than to morphine. In conclusion, the 118A>G substitution alters receptor responses to opioids through variable C‐terminal domain movements that are agonist and splice variant dependent.